Ansiedad dental y autoestima en pacientes pediátricos con ortopedia maxilofacial - Barreiro Mendoza, Gema Nataly (2023)
The main repercussions of malocclusion could be linked to emotional and social well-being. Dental anxiety and self-esteem are emotions, prevalent in problems related to oral health. However, no studies of emotions in children with maxillofacial orthopedics have been performed. Psychometrics allows a reliable evaluation of psychosocial repercussions in an individual. The HTP projective test (house: house, tree: tree and person: person) requires that the evaluated individual make a drawing. The drawing technique presents reliability, validity and is consistent. From the above and in view of the existing information, it is necessary to review the HTP technique, its use and contribution in maxillofacial orthopedics. For this reason, the objective of this study was to analyze dental anxiety and self-esteem in pediatric patients with maxillofacial ortho pedic treatment. The method used was bibliographic review and content analysis. It was possible to determine that a maxillofacial orthopedist must fully master the oral health of children, its psychosocial influence and the use of adequate techniques to diagnose and manage their behavior, which contributes to an optimal doctor- patient / family relationship and mitigates non-compliance with the therapeutic indications, achieving success in the treatment.